Analysis of the Spiritual Experience of Performing Umrah for Converts to Islam (Phenomenological Study in Muallaf Kita Bersama Semarang City) - Hakim, Lukman; Muhajarah, Kurnia (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
The spiritual experience experienced by converts in performing Umrah is certainly different from the spiritual experience experienced by Muslims who were born and raised in an Islamic environment. The spiritual experience of converts is more complex and dynamic, because it is influenced by various factors, such as background, motivation, expectations, and the challenges they face. This spiritual experience was studied using a phenomenological approach. The subjects of this study were 5 converts who had performed Umrah in the MKB community. The method and data collection tools in this research are interviews. And for the results of interviews and observations described in descriptive form. According to the results of data analysis that has been carried out in the results and discussion, the author can draw conclusions, namely: Converts who perform Umrah have aspects of spiritual experience described by William James, namely aspects of ineffability expressed through feelings of amazement and difficult to explain by words when arriving at the Kabah area and kissing Hajar Aswad, aspects of noetic quality expressed through feelings such as there are supernatural worshipers who help to kiss Hajar Aswad, The transiency aspect is expressed through feelings of anxiety and suddenly crying when reminded of the sins that have been committed, and the passivity aspect is expressed through focusing only on Allah SWT by dhikr and asking for forgiveness.